RESTORATIVE JUSTICE IN THE NEW CRIMINAL CODE AS A MANIFESTATION OF PROPHETIC LAW VALUES AND PANCASILA - Sugiarto, Bagas Tri (Tazir, 2025)
This research aims to explain the extent to which the principle of restorative justice in the 2023 Criminal Code reflects prophetic legal values and how their implications are for the practice of Pancasila values. This study adopts a normative juridical methodology combined with a descriptive-analytical approach. Data is collected through literature review including primary, secondary, and tertiary legal sources, and then processed qualitatively. The results show that the application of restorative justice in the 2023 Criminal Code is in line with three main values in the prophetic legal framework, namely the dimensions of divinity, humanity, and justice. This approach also reflects the practice of Pancasila values, especially in upholding human dignity, deliberation, and social justice. Thus, the 2023 Criminal Code not only represents the renewal of the national criminal law, but also becomes a forum for humanist and transformative legal transformation based on the noble values of the nation.